Pengaruh Perencanaan Pengadaan Penerimaan dan Penyimpanan Obat terhadap Kualitas Pelayanan di Instalasi Farmasi Rumah Sakit Umum Daerah Provinsi Papua Barat - Ittang Somba; Kosasih Kosasih; Ayu Laili Rahmiyati; Vip Paramarta; Taufan Nugroho (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the impact of planning, procurement, receipt, and storage of medicines on pharmaceutical service quality at the Pharmacy Installation of the Regional General Hospital of West Papua Province. The research uses a quantitative approach with an explanatory design, analyzing primary and secondary data obtained through interviews and questionnaires from 100 respondents. Descriptive analysis results show that the quality of pharmaceutical management in this hospital is categorized as "Adequate". Planning, with a coefficient of 0.183 and a t-value of 2.672, shows a significant impact on service quality. Procurement of medicines, though categorized as "Adequate," has a coefficient of 0.157 with a t-value of 1.814, which is also significant. Receipt of medicines is the most dominant variable with a coefficient of 0.636 and a t-value of 7.532, indicating a very significant impact. Storage of medicines also significantly affects service quality, with a coefficient of 0.291 and a t-value of 7.532. The study highlights the importance of effective management at each stage of pharmaceutical management to improve service quality in hospitals, particularly in the aspects of receipt and storage of medicines.